2021
DOI: 10.1097/ede.0000000000001334
|View full text |Cite
|
Sign up to set email alerts
|

Helped into Harm

Abstract: Background: Interventions can have harmful effects among subgroups they intend to help. The Moving To Opportunity experiment, in which families were randomized to receive a Section 8 housing voucher, was one example. Voucher receipt generally resulted in better long-term mental health and lower substance use and risk behavior outcomes among adolescent girls, but resulted in worse outcomes among adolescent boys. Reasons for this discrepancy and the unintended harmful health effects for boys are unclear. We used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 62 publications
1
18
0
Order By: Relevance
“…This finding provides vital clues for intervention research and suggests that ambitious trials are now warranted to investigate whether moving people out of more deprived environments can ameliorate SMI risk. To our knowledge, no trial has tested such interventions regarding SMI, although the Moving to Opportunity trial has shown evidence that moving to higher-quality neighborhoods resulted in lower psychological distress in adolescence, although this may also have introduced unintended harms for some groups, including increased mental health risks for boys …”
Section: Discussionmentioning
confidence: 99%
“…This finding provides vital clues for intervention research and suggests that ambitious trials are now warranted to investigate whether moving people out of more deprived environments can ameliorate SMI risk. To our knowledge, no trial has tested such interventions regarding SMI, although the Moving to Opportunity trial has shown evidence that moving to higher-quality neighborhoods resulted in lower psychological distress in adolescence, although this may also have introduced unintended harms for some groups, including increased mental health risks for boys …”
Section: Discussionmentioning
confidence: 99%
“…Intuitively, natural effects assess the causal effects of treatment mediated (indirect) or not mediated (direct) through some mediator(s) by fixing the mediator to the specific value it would have taken under treatment or no treatment. Despite natural effects' appealing qualities, Rudolph et al 7 eschew them for good reason. Natural effects require strong identification assumptions 9,11,12 and are difficult to interpret: 13 in this situation, the natural direct effect, for example, would be a contrast between the probability of a given behavioral or substance use outcome had every boy's family not received a voucher, and the probability of the outcome had all families received vouchers although each boy was exposed to the school, neighborhood, and social environments he would have lived in had his family not received a voucher.…”
Section: Choosing An Estimandmentioning
confidence: 99%
“…In addition, controlled direct effects have limited utility if the goal is to quantify the mediated portion of the total effect, as there are generally no corresponding indirect effects, 15,16 although the contrast between the direct and total effects can be conceptualized as the portion of the harmful effect eliminated by a policy intervention. 17 Although natural effects can be used to ask and answer theoretical questions about mechanisms, and controlled direct effects about a possibly radical intervention on the mediator, the stochastic effects Rudolph et al 7 estimate fall somewhere in between. Instead of assigning each boy to the environment he would have experienced in the absence of a housing voucher or all boys to the same environment, these estimands instead apply distributional interventions on the mediator.…”
Section: Choosing An Estimandmentioning
confidence: 99%
See 2 more Smart Citations